The Concept and Development of Takaful Insurance in the Framework of Sharia Economic Law - J Jamaluddin (Walidem Institute and Publishing (WIP), 2024)
Allah Almighty has fully established the Sharia laws relating to the field of worship and creed. Establishing the Shari'a is always based on the general principles of Shari'a actions, not burdensome, not increasing the burden, and gradually. Establishing laws is also in line with the good of the crowd. The establishment of Islamic law is divided into two forms, namely dhanny, and qatiiyah. Dhanni is a law whose nature has not been able to fulfil its one hundred per cent capacity of truth in a matter. This problem is not closed to the possibility for jurisprudence scientists to differ in views on the legal status. The so-called qat’iyah is a law that is true and also has a clear purpose, so there is no way for dissent. Problems arise with the development of time. Man needs protection that can protect himself or one's soul. It is necessary to have a company that can provide guarantees or guarantees for oneself or one's soul. The company is in the form of insurance. The research aims to analyze insurance laws that are developing today. This article is classified as literature research with a qualitative approach. The methodology used is an empirical juridical study. The results of the study concluded that as long as the insurance is applied there is no element of usury, element of maisir, and element of fraud, it is permissible in Islam.